ANALISIS SEMIOTIKA SLOGAN MONDHUK ENTAR NGABDI BEN NGAJI BAGI SANTRI PONDOK PESANTREN SALAFIYAH SYAFI’IYAH SUKOREJO SITUBONDO - Shofiyatul Khoiriyah; Wisri (Maddah : Jurnal Komunikasi dan Konseling Islam, 2023)
This paper discusses the slogan “Mondhuk Entar Ngabdi ben Ngaji” which is the slogan used by the caretaker of the Salafiyah Syafi’iyah Islamic Boarding School K. H. R. Ach. Azaim Ibrahimy because he saw the changing times that threaten the morals of students. So he used this slogan to teach his students to always serve and recite the Koran. He also used this slogan to remind students of their intention to enter Islamic boarding schools, namely serving and reciting the Koran. In this study, researchers used semiotic analysis methods. Semiotics is a science that studies signs. Signs are the basis of the communication process. Signs will never be separated from the communication process. Because every time the communication process takes place either the communicator or the communicant will produce and interpret signs from each other. And the activities of producing and interpreting signs are called semiotics. The purpose of this study is to reveal the true meaning of the slogan “Mondhuk Entar Ngabdi ben Ngaji” for students. So that students can know its meaning and practice it. In addition, this study also aims to find the impact of the slogan on students. The result is that the meaning of the slogan “Mondhuk Entar Ngabdi ben Ngaji” for the students of the Salafiyah Syafi’iyah Islamic Boarding School is that the true intention of boarding for them is to serve and recite the Koran.